MICROSATELLITES-BASED EVALUATION OF THE PEAR CULTIVARS SELECTED FROM NIKITSKY BOTANICAL GARDENS GERMPLASM BY THEIR ECONOMICALLY VALUABLE CHARACTERISTICS - Y. V. Plugatar; R. D. Babina; I. I. Suprun; T. S. Naumenko; Y. I. Alekseev (Вавиловский журнал генетики и селекции)
Mobilization and preservation of genetic sources of diversity of the cultivated pear varieties and their wild relatives is one of the main aspects of new cultivars breeding for modern intensive horticulture. The crucial matter during a new cultivar creation goes to the selection of parental pairs, which obtain a complex of positive features. The aim of this work is to study the Gene Fund collection of pear plantings from Nikitsky Botanical Gardens in accordance with the main economically important traits and to select the most valuable genotypes for using them in breeding programs as a starting material, as well as to conduct a DNA-fingerprinting and the analyses of genetic polymorphism of promising cultivars from the collection of pear with implementing of microsatellite analyses. As a result of long-term studies the following cultivars were selected in accordance with the complex of features promising for the breeding program: Gvardeiskaya Zimnyaya, Izuminka Kryma, Izumrudnaya, Kelmenchanka, Krymskaya Aromatnaya, Krymskaya Medovaya, Lazurnaya, Maria, Mriya, Nadezhda Stepi, Nezabudka, Novosadovskaya, Oreanda Kryma, Otechestvennaya, Tauschaya, Yakimovskaya. The samples of these cultivars were forwarded for genotyping. For the genetic polymorphism analyses of the studied cultivars, seven microsatellite DNA-markers – EMPc108, EMPc117, EMPc115, CH04e03 and CH01d09, CH01f07a, CH01d08 – grouped into 2 multiplex sets were used. The SSR-markers were significantly different according to their level of polymorphism – from 3 (CH04e03 marker) to 11 (EMPc115) alleles per a gene locus were revealed, the effective number of alleles varying from 1.37 to 4.65. Based on SSR-markers polymorphism analysis data, the rate of genetic similarity of the studied pear cultivars was estimated. This evaluation research helped estimate genetic relations inside the studied sample collection of genotypes. The SSR-fingerprints of the cultivars obtained will be used as a starting material for the creation of DNA-passports database of the “NBG – NSC” Gene Fund collection of pear cultivars.